Socioeconomic Drivers of PM(2.5) in the Accumulation Phase of Air Pollution Episodes in the Yangtze River Delta of China - Lou, Cai-Rong (Int J Environ Res Public Health, 2016)
Recent studies in PM(2.5) sources show that anthropogenic emissions are the main contributors to haze pollution. Due to their essential roles in establishing policies for improving air quality, socioeconomic drivers of PM(2.5) levels have attracted increasing attention. Unlike previous studies focusing on the annual PM(2.5) concentration (C(year)), this paper focuses on the accumulation phase of PM(2.5) during the pollution episode (PMAE) in the Yangtze River Delta in China. This paper mainly explores the spatial variations of PMAE and its links to the socioeconomic factors using a geographical detector and simple linear regression. The results indicated that PM(2.5) was more likely to accumulate in more developed cities, such as Nanjing and Shanghai. Compared with C(year), PMAE was more sensitive to socioeconomic impacts. Among the twelve indicators chosen for this study, population density was an especially critical factor that could affect the accumulation of PM(2.5) dramatically and accounted for the regional difference. A 1% increase in population density could cause a 0.167% rise in the maximal increment and a 0.214% rise in the daily increase rate of PM(2.5). Additionally, industry, energy consumption, and vehicles were also significantly associated with PM(2.5) accumulation. These conclusions could serve to remediate the severe PM(2.5) pollution in China.